GENERAL OVERVIEW TO STUDENT-CENTERED APPROACH - Babayev Javid (Modern Scientific Method, 2024)
The article elaborates student-centered instruction and its characteristic features. This approach is compared with teacher-centered instruction. Clarity has been brought to the notion “center”. Besides, language teaching methods which require student-centered instruction and teacher-centered instruction have been involved in the study. It has been concluded that the teacher has a partial control over the students at the lesson while conducting the lesson via student-centered focus though the students organize the whole lesson in the classroom. Topics are usually chosen by the students while the materials are given by the teacher.